2019
DOI: 10.1371/journal.pone.0210329
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk prediction models for women in the general population: A systematic review

Abstract: AimTo provide a comprehensive overview of cardiovascular disease (CVD) risk prediction models for women and models that include female-specific predictors.MethodsWe performed a systematic review of CVD risk prediction models for women in the general population by updating a previous review. We searched Medline and Embase up to July 2017 and included studies in which; (a) a new model was developed, (b) an existing model was validated, or (c) a predictor was added to an existing model.ResultsA total of 285 predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
0
24
0
2
Order By: Relevance
“…Prediction models for traditional risk factors for cardiovascular disease could underestimate the true risk of cardiovascular disease in young women because they do not account for risk factors specific to women 155. A recent systematic review on risk prediction models for cardiovascular disease in women noted that only 1.1% of the 260 articles included in the review investigated the added value of incorporating risk factors specific to women in risk prediction models 156. Even in studies that evaluated the use of predictors specific to women, however, none included predictors such as hypertensive disorders of pregnancy, gestational diabetes, polycystic ovary syndrome, and premature ovarian insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models for traditional risk factors for cardiovascular disease could underestimate the true risk of cardiovascular disease in young women because they do not account for risk factors specific to women 155. A recent systematic review on risk prediction models for cardiovascular disease in women noted that only 1.1% of the 260 articles included in the review investigated the added value of incorporating risk factors specific to women in risk prediction models 156. Even in studies that evaluated the use of predictors specific to women, however, none included predictors such as hypertensive disorders of pregnancy, gestational diabetes, polycystic ovary syndrome, and premature ovarian insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of these factors to improve cardiovascular disease risk prediction in women has not been previously evaluated. 48 Moreover, a systematic review of risk prediction models in women in the general population concluded that established sex independent cardio vascular disease risk predictors (ie, age, blood pressure, and smoking) made the greatest contribution to model performance. 48 Second, although we accounted for differences in risk factor burden when examining use of primary and secondary prevention medicines, we were unable to account for differences in eligibility for or contraindi cations to specific medicines.…”
Section: Discussionmentioning
confidence: 99%
“…155 A recent systematic review on risk prediction models for cardiovascular disease in women noted that only 1.1% of the 260 articles included in the review investigated the added value of incorporating risk factors specific to women in risk prediction models. 156 Even in studies that evaluated the use of predictors specific to women, however, none included predictors such as hypertensive disorders of pregnancy, gestational diabetes, polycystic ovary syndrome, and premature ovarian insufficiency. The benefit of adding reproductive factors to risk prediction models for cardiovascular disease needs to be extensively evaluated.…”
Section: Adverse Pregnancy Outcomesmentioning
confidence: 99%